Kinetics of Oxidation of Aldehydes in Absence and Presence of Surfactants - Ahmad, Firoz; Abbas Siddiqui, M. (Asian Journal of Chemistry, 2016)
The kinetics of oxidation of aldehydes by bromate in the absence of any surfactant has been studied and compared with the kinetic parameters observed in the presence of anionic surfactant of sodium dodecylsulphate (SDS) and cationic surfactant of cetylpyridinium chloride (CPC). The observed rate law is –d[BrO3–]/dt = k' [Aldehyde][BrO3–] where k' is a complex function of hydrogen ion concentration and surfactant concentration.